COST-EFFECTIVENESS OF RENAL DENERVATION THERAPY FOR TREATMENT RESISTANT HYPERTENSION: A BEST CASE SCENARIO - Chowdhury, E.; Reid, Christopher; Zoomer, E.; Kelly, D.; Liew, D. (LIPPINCOTT WILLIAMS & WILKINS, 2018)
No Abstract Available